Education on the Implementation of Epidemiological Surveillance for HIV/AIDS Infectious Diseases in the Community at the Ledeunu Community Health Center, Sabu Raijua Regency - Oktofianus Radja Tuka; Nurwijayanti (Universitas STRADA Indonesia, 2024)
HIV/AIDS epidemiological surveillance is a series of continuous, systematic and ongoing observation processes in data collection, analysis and interpretation of HIV/AIDS disease data in an effort to effectively and efficiently prevent and control HIV/AIDS. The aim of implementing this Community Service activity is to educate the community so that they can overcome the possibility of HIV/AIDS and how to treat it. The activity was carried out in the Ledeunu health center working area using a lecture method by the implementing team, attended by community members, accompanied by the distribution of prizes to each participant. The material presented is evaluated by conducting a question and answer session at the end of the activity, where all questions/quizzes submitted by the implementing team can be answered by the participants.